2020
DOI: 10.7759/cureus.10316
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Differences of COVID-19 Over the World

Abstract: Background Coronavirus disease 2019 (COVID-19), originally, from Wuhan, China, has now spread to most countries across the globe and devastated global healthcare systems. The impact of this disease has, however, shown baffling variations in prevalence in different regions of the world. The aim of this short review is to identify differential national COVID-19 prevalence of COVID-19, as well as to suggest these epidemiological differences. Methods A review of studies was conducted using PubMed and Google Schola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
1
9
0
1
Order By: Relevance
“…SARS-CoV-2 continues to affect every region of the world, but some countries are experiencing high rates of infection, while others appear to have mostly controlled the virus. 10 It's well documented that many patients may have been contaminated person to person by asymptomatic patients. Therefore, asymptomatic patients can be considered as a source of infection and they can spread the virus, and consequently, large-scale transmission from asymptomatic patients is suspected.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 continues to affect every region of the world, but some countries are experiencing high rates of infection, while others appear to have mostly controlled the virus. 10 It's well documented that many patients may have been contaminated person to person by asymptomatic patients. Therefore, asymptomatic patients can be considered as a source of infection and they can spread the virus, and consequently, large-scale transmission from asymptomatic patients is suspected.…”
Section: Discussionmentioning
confidence: 99%
“…Escobar et al performed an epidemiological study, after eliminating the potential confounding factors such as the COVID-19 epidemic stages, geographical distribution, population density, and age structure, they found a 10% increase in the BCG index resulted in a 10.4% decrease in COVID-19 deaths [88] . Interestingly, a large number of subsequent ecological studies have found a similar phenomenon that BCG vaccination rates and years of implementation of the BCG vaccination policy are significantly negatively correlated with COVID-19 morbidity and mortality [14] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] , [104] , [105] , [106] , [107] , [108] , [109] , [110] , [111] , [112] , [113] .…”
Section: Is the Bcg Vaccine Effective Against Sars-cov-2 Infection?mentioning
confidence: 99%
“…In the early months of the COVID-19 pandemic, findings from the ecological and analytical studies indicated that countries with low BCG coverage had significantly higher rates of COVID-19 morbidity and mortality than countries with high BCG coverage . On the contrary, other ecological and analytical studies found that BCG vaccination could not provide adequate protection against COVID-19 infection (41)(42)(43)(44)(45)(46)(47)(48)(49)(50). The results of these ecological and analytical studies were contradictory, and the heterogeneity of these findings may originate from some confounding factors, such as population density, ethnicity, age structure, income, healthcare access and quality index, COVID-19 transmission progression, COVID-19 testing rate, nonpharmaceutical interventions, and geographical distribution (2, 5, 51-53).…”
Section: Early Evidence On Bcg Prevention Of Covid-19mentioning
confidence: 99%